Drivers of retail app continuance use intention among Malaysian millennials - Lim, Xin Jean (2020)
The rise of the “always-on, constantly connected” shopper due to the tremendous increase in the global adoption of smartphones has led to the growth of mobile dominated marketing. Owing to this trend, retailers have embraced the retail app as one of the essential components to expand online marketing and establish a long-term brand-building advantage. The retail app is quickly catching up as an important communication tool in contemporary marketing that maximizes convenience, delivers notifications to consumers, and strengthens the retailer consumer relationship. Despite the proliferation of the retail app as an invaluable marketing resource, continued use among consumers has become a significant issue that hinders the growth of online marketing. Responding to the calls of earlier researchers, the main purpose of this study was to examine the features that impact retail app continuance use intention among Millennial mobile shoppers in Malaysia. First, underpinned by the Two-Factor Theory, marketing mix and anthropomorphism presence were suggested as the hygiene and motivation factors that encourage consumers to continue using a retail app. Second, the Stimulus-Organism-Response (S-O-R) Model was applied to explain the mediating role of customer engagement. Third, the Regulatory Focus Theory was adopted to investigate the moderating roles of prevention and promotion focus. Data was collected using the purposive sampling approach to identify respondents who were Malaysian Millennial mobile shoppers (born after the year 1981) and had used a retail app in the past six months. Overall, 456 responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Three notable findings were found in this study: 1) marketing mix was positively related to retail app continuance use intention, while anthropomorphism presence was not; 2) customer engagement mediated the influences of anthropomorphism presence and marketing mix on continuance use intention, indicating the indispensable role of engagement; and 3) Millennial consumers with a high prevention focus tended to put more emphasis on marketing mix components in the engagement process. Apart from advancing the literature, this study offers substantial contributions to practitioners. First, retailers should be aware that the effectiveness of app features depends primarily on their effectiveness in engaging with consumers. Second, information system managers (i.e. app developers) are suggested to update and embed more humanized features within apps for optimal results. Finally, policymakers are a key stakeholder group who affect the development of retail apps. Their assistance is seen as a catalyst that facilitates retailers’ move towards digitalization. Despite this study’s interesting findings, there are several limitations that should be noted. Since this study targeted a specific country, future studies are recommended to extend the model and conduct comparative studies to understand the way cultural differences impact retail app usage. Additionally, the insignificant finding between anthropomorphism presence and continuance use intention suggests the need for further research. Thus, it would be useful to examine how privacy concern moderates this relationship. Also, this study focused on respondents' perceptions of retail apps in general. Hence, scholars are recommended to conduct experimental research to better understand consumer perceptions of specific types of retail apps.